Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Produktifitas Kerja Pegawai Non PNS Di Kantor Satuan Polisi Pamong Praja (SATPOL PP) Kota Solok - Adtri Agusman; Esi Sriyanti; Netti Indrawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research was conducted at the Office of the Civil Service Police Unit (Satpol PP) Solok City. The purpose of this study was to determine whether Work Discipline and Compensation had an effect on the Work Productivity of Non-PNS Employees at the Office of the Praja Police Unit (Satpol PP) Solok City. The research method used is the Total Sampling technique, namely the number of samples is the same as the population. From the population taken as many as 77 respondents, data collection methods using observation, interviews and questionnaires. The results of the multiple linear regression coefficient test can be the equation Y = 12.727 + 0.361 X1 + 0.312 (X2), it can be said that the independent variables are Work Discipline and Compensation together have a positive sign in the direction of the Work Productivity of Non-PNS Employees at the Solok City Satpol PP Office. The results of the coefficient of determination (R2) obtained a value of 0.267 that the contribution between the variables of Work Discipline and Compensation of 0.267 or 26.7% and influenced by other variables (100-0,267) was % of variables not examined in this study such as satisfaction, attitudes, behavior, training and willingness to work. The results of the tcount of Work Discipline are 2,631 > 1,992, which means that the Work Discipline variable (X1) has an effect and is significant on Work Productivity (Y). The result of t-count Compensation (X2) is 2.391 > 1.992, which means that the Compensation variable has an effect and is significant on Work Productivity. And the results of the f test are 13,499 > f table 3,12 with a significant level of 0.000 < 0.05. The large fcount value of the ftable value and a significant value less than 0.05 indicates that Work Discipline (X1) and Compensation (X2) simultaneously or jointly have a significant and significant effect on the dependent variable, namely Work Productivity.